Population phase-dependent niche requirements may limit outbreaks of the range-expanding mountain pine beetle in the western boreal forest - Stanley W. Pokorny; Brian H. Aukema; Kenneth F. Raffa; Allan L. Carroll (Forest Ecology and Management, 2025)

What Is a Specialist? Quantifying Host Breadth Enables Impact Prediction for Invasive Herbivores - Ashley N. Schulz; Nathan P. Havill; Travis D. Marsico; Matthew P. Ayres; Kamal J.K. Gandhi; Daniel A. Herms; Angela M. Hoover; Ruth A. Hufbauer; Andrew M. Liebhold; Kenneth F. Raffa; Kathryn A. Thomas; Patrick C. Tobin; et al. (Ecology Letters, 2025)
Herbivores are commonly classified as host specialists or generalists for various purposes, yet the definitions of these terms, and their intermediates, are often imprecise and ambiguous. We quantified host breadth for 240 non‐native, tree‐feeding insects in North America using phylogenetic diversity. We demonstrated that a partitioning of host breadth: (1) causes 67% of non‐native insects to shift from a generalist to specialist category, (2) displays a reduction in host breadth from the native to introduced range, (3) identifies an inflection point in a model predicting the likelihood of non‐native insect ecological impact, with a corresponding change in behaviour associated with specialists versus generalists, and (4) enables three models for strong prediction of whether a non‐native forest insect will cause high impacts. Together, these results highlight the primacy of how herbivore host recognition and plant defences mediate whether novel host interactions will result in high impact after invasion.

Quantification of heritable variation in multiple lodgepole pine chemical and physical traits that contribute to defense against mountain pine beetle (Dendroctonus ponderosae) - Michael Howe; Alvin Yanchuk; Kimberly F. Wallin; Kenneth F. Raffa (Forest Ecology and Management, 2024)

Numbers matter: how irruptive bark beetles initiate transition to self-sustaining behavior during landscape-altering outbreaks - Michael Howe; Kenneth F. Raffa; Brian H. Aukema; Claudio Gratton; Allan L. Carroll (Oecologia, 2022)

Predicting non-native insect impact: focusing on the trees to see the forest - Ashley N. Schulz; Angela M. Mech; Matthew P. Ayres; Kamal J. K. Gandhi; Nathan P. Havill; Daniel A. Herms; Angela M. Hoover; Ruth A. Hufbauer; Andrew M. Liebhold; Travis D. Marsico; Kenneth F. Raffa; Patrick C. Tobin; et al. (Biological Invasions, 2021)

Climate‐induced outbreaks in high‐elevation pines are driven primarily by immigration of bark beetles from historical hosts - Michael Howe; Allan Carroll; Claudio Gratton; Kenneth F. Raffa (Global Change Biology, 2021)
Warming temperatures are allowing native insect herbivores to expand into regions that previously exceeded their thermal tolerance, encounter new host species, and pose significant threats to native communities. However, the dynamics of these expansions remain poorly understood, particularly in the extent to which outbreaks remain reliant on emigration from historical hosts or are driven by local reproduction within novel hosts in the expanded range. We tested these non‐mutually exclusive hypotheses using spatially explicit data on mountain pine beetle ( Dendroctonus ponderosae ), which historically undergoes intermittent outbreaks in low‐elevation lodgepole pine ( Pinus contorta ), but is now causing severe mortality in a high‐elevation endangered species, whitebark pine ( Pinus albicaulis ). We compiled data from 2000 to 2019 across British Columbia, Canada, at 1‐km 2 resolution, and analyzed spatiotemporal patterns of beetle infestations, lodgepole pine distributions, expansion into habitats dominated by whitebark pine, and the likelihood of future outbreaks in all pine communities under simulated conditions. Overall, we found strong support for the hypothesis of emigration from the historical host species continuing to be a major driver of outbreaks in the more recently accessed host. First, beetle population pressure was consistently the best predictor of infestation severity in both lodgepole and whitebark pine, and appeared to be mostly unidirectional from lodgepole to whitebark pine. Second, infestations in lodgepole pine were of a longer duration than those in whitebark pine, which appeared too brief to sustain transitions from endemic to eruptive dynamics. Furthermore, resource depletion appears to drive emigration from lodgepole pine, whereas in whitebark pine drought appears to favor establishment of immigrants although bioclimatic factors and stand structure preclude self‐sustaining outbreaks. Finally, we project that most pine in British Columbia will be at risk in the event of a new major outbreak. We describe implications for conserving and protecting whitebark pine and to other climate‐driven range expansions.

Bark Beetle Outbreaks in Europe: State of Knowledge and Ways Forward for Management - Tomáš Hlásny; Louis König; Paal Krokene; Marcus Lindner; Claire Montagné-Huck; Jörg Müller; Hua Qin; Kenneth F. Raffa; Mart-Jan Schelhaas; Miroslav Svoboda; Heli Viiri; Rupert Seidl (Current Forestry Reports, 2021)

Root Secondary Metabolites in Populus tremuloides: Effects of Simulated Climate Warming, Defoliation, and Genotype - Zhengzhen Li; Kennedy F. Rubert-Nason; Mary A. Jamieson; Kenneth F. Raffa; Richard L. Lindroth (Journal of Chemical Ecology, 2021)

Drought-Mediated Changes in Tree Physiological Processes Weaken Tree Defenses to Bark Beetle Attack - Thomas Kolb; Ken Keefover-Ring; Stephen J. Burr; Richard Hofstetter; Monica Gaylord; Kenneth F. Raffa (Journal of Chemical Ecology, 2019)

Genetic variation in aspen phytochemical patterns structures windows of opportunity for gypsy moth larvae - Michael A. Falk; Richard L. Lindroth; Ken Keefover-Ring; Kenneth F. Raffa (Oecologia, 2018)

Interactions between Bacteria And Aspen Defense Chemicals at the Phyllosphere – Herbivore Interface - Charles J. Mason; Tiffany M. Lowe-Power; Kennedy F. Rubert-Nason; Richard L. Lindroth; Kenneth F. Raffa (Journal of Chemical Ecology, 2016)

Rapid Induction of Multiple Terpenoid Groups by Ponderosa Pine in Response to Bark Beetle-Associated Fungi - Ken Keefover-Ring; Amy Trowbridge; Charles J. Mason; Kenneth F. Raffa (Journal of Chemical Ecology, 2016)

Bacteria influence mountain pine beetle brood development through interactions with symbiotic and antagonistic fungi: implications for climate-driven host range expansion - Janet Therrien; Charles J. Mason; Jonathan A. Cale; Aaron Adams; Brian H. Aukema; Cameron R. Currie; Kenneth F. Raffa; Nadir Erbilgin (Oecologia, 2015)

Experimental climate warming alters aspen and birch phytochemistry and performance traits for an outbreak insect herbivore - Mary A. Jamieson; Ezra G. Schwartzberg; Kenneth F. Raffa; Peter B. Reich; Richard L. Lindroth (Global Change Biology, 2015)
Climate change and insect outbreaks are key factors contributing to regional and global patterns of increased tree mortality. While links between these environmental stressors have been established, our understanding of the mechanisms by which elevated temperature may affect tree–insect interactions is limited. Using a forest warming mesocosm, we investigated the influence of elevated temperature on phytochemistry, tree resistance traits, and insect performance. Specifically, we examined warming effects on forest tent caterpillar ( Malacosoma disstria ) and host trees aspen ( Populus tremuloides ) and birch ( Betula papyrifera ). Trees were grown under one of three temperature treatments (ambient, +1.7 °C, +3.4 °C) in a multiyear open‐air warming experiment. In the third and fourth years of warming (2011, 2012), we assessed foliar nutrients and defense chemistry. Elevated temperatures altered foliar nitrogen, carbohydrates, lignin, and condensed tannins, with differences in responses between species and years. In 2012, we performed bioassays using a common environment approach to evaluate plant‐mediated indirect warming effects on larval performance. Warming resulted in decreased food conversion efficiency and increased consumption, ultimately with minimal effect on larval development and biomass. These changes suggest that insects exhibited compensatory feeding due to reduced host quality. Within the context of observed phytochemical variation, primary metabolites were stronger predictors of insect performance than secondary metabolites. Between‐year differences in phytochemical shifts corresponded with substantially different weather conditions during these two years. By sampling across years within an ecologically realistic and environmentally open setting, our study demonstrates that plant and insect responses to warming can be temporally variable and context dependent. Results indicate that elevated temperatures can alter phytochemistry, tree resistance traits, and herbivore feeding, but that annual weather variability may modulate warming effects leading to uncertain consequences for plant–insect interactions with projected climate change.

Contrasting Patterns of Diterpene Acid Induction by Red Pine and White Spruce to Simulated Bark Beetle Attack, and Interspecific Differences in Sensitivity Among Fungal Associates - Charles J. Mason; Kier D. Klepzig; Brian J. Kopper; Philip J. Kersten; Barbara L. Illman; Kenneth F. Raffa (Journal of Chemical Ecology, 2015)

Aspen Defense Chemicals Influence Midgut Bacterial Community Composition of Gypsy Moth - Charles J. Mason; Kennedy F. Rubert-Nason; Richard L. Lindroth; Kenneth F. Raffa (Journal of Chemical Ecology, 2015)

Influence of Diet and Density on Laboratory Cannibalism Behaviors in Gypsy Moth Larvae (Lymantria dispar L.) - Charles J. Mason; Zachary Cannizzo; Kenneth F. Raffa (Journal of Insect Behavior, 2014)

Simulated climate warming alters phenological synchrony between an outbreak insect herbivore and host trees - Ezra G. Schwartzberg; Mary A. Jamieson; Kenneth F. Raffa; Peter B. Reich; Rebecca A. Montgomery; Richard L. Lindroth (Oecologia, 2014)

Plant-associated bacteria degrade defense chemicals and reduce their adverse effects on an insect defoliator - Charles J. Mason; John J. Couture; Kenneth F. Raffa (Oecologia, 2014)

A Tale of Convergence - Kenneth F. Raffa (Journal of Chemical Ecology, 2014)

Terpenes Tell Different Tales at Different Scales: Glimpses into the Chemical Ecology of Conifer - Bark Beetle - Microbial Interactions - Kenneth F. Raffa (Journal of Chemical Ecology, 2014)

Bacteria Associated with a Tree-Killing Insect Reduce Concentrations of Plant Defense Compounds - Celia K. Boone; Ken Keefover-Ring; Abigail C. Mapes; Aaron S. Adams; Jörg Bohlmann; Kenneth F. Raffa (Journal of Chemical Ecology, 2013)

What explains landscape patterns of tree mortality caused by bark beetle outbreaks in Greater Yellowstone? - Martin Simard; Erinn N. Powell; Kenneth F. Raffa; Monica G. Turner (Global Ecology and Biogeography, 2012)
Aim Bark beetle outbreaks have recently affected extensive areas of western North American forests, and factors explaining landscape patterns of tree mortality are poorly understood. The objective of this study was to determine the relative importance of stand structure, topography, soil characteristics, landscape context (the characteristics of the landscape surrounding the focal stand) and beetle pressure (the abundance of local beetle population eruptions around the focal stand a few years before the outbreak) to explain landscape patterns of tree mortality during outbreaks of three species: the mountain pine beetle, which attacks lodgepole pine and whitebark pine; the spruce beetle, which feeds on Engelmann spruce; and the Douglas‐fir beetle, which attacks Douglas‐fir. A second objective was to identify common variables that explain tree mortality among beetle–tree host pairings during outbreaks. Location Greater Yellowstone ecosystem, Wyoming, USA. Methods We used field surveys to quantify stand structure, soil characteristics and topography at the plot level in susceptible stands of each forest type showing different severities of infestation (0–98% mortality; n = 129 plots). We then used forest cover and beetle infestation maps derived from remote sensing to develop landscape context and beetle pressure metrics at different spatial scales. Plot‐level and landscape‐level variables were used to explain outbreak severity. Results Engelmann spruce and Douglas‐fir mortality were best predicted using landscape‐level variables alone. Lodgepole pine mortality was best predicted by both landscape‐level and plot‐level variables. Whitebark pine mortality was best – although poorly – predicted by plot‐level variables. Models including landscape context and beetle pressure were much better at predicting outbreak severity than models that only included plot‐level measures, except for whitebark pine. Main conclusions Landscape‐level variables, particularly beetle pressure, were the most consistent predictors of subsequent outbreak severity within susceptible stands of all four host species. These results may help forest managers identify vulnerable locations during ongoing outbreaks.

Effects of biotic disturbances on forest carbon cycling in the U nited S tates and C anada - Jeffrey A. Hicke; Craig D. Allen; Ankur R. Desai; Michael C. Dietze; Ronald J. Hall; Edward H. (Ted) Hogg; Daniel M. Kashian; David Moore; Kenneth F. Raffa; Rona N. Sturrock; James Vogelmann (Global Change Biology, 2012)
Forest insects and pathogens are major disturbance agents that have affected millions of hectares in N orth A merica in recent decades, implying significant impacts to the carbon ( C ) cycle. Here, we review and synthesize published studies of the effects of biotic disturbances on forest C cycling in the U nited S tates and C anada. Primary productivity in stands was reduced, sometimes considerably, immediately following insect or pathogen attack. After repeated growth reductions caused by some insects or pathogens or a single infestation by some bark beetle species, tree mortality occurred, altering productivity and decomposition. In the years following disturbance, primary productivity in some cases increased rapidly as a result of enhanced growth by surviving vegetation, and in other cases increased slowly because of lower forest regrowth. In the decades following tree mortality, decomposition increased as a result of the large amount of dead organic matter. Net ecosystem productivity decreased immediately following attack, with some studies reporting a switch to a C source to the atmosphere, and increased afterward as the forest regrew and dead organic matter decomposed. Large variability in C cycle responses arose from several factors, including type of insect or pathogen, time since disturbance, number of trees affected, and capacity of remaining vegetation to increase growth rates following outbreak. We identified significant knowledge gaps, including limited understanding of carbon cycle impacts among different biotic disturbance types (particularly pathogens), their impacts at landscape and regional scales, and limited capacity to predict disturbance events and their consequences for carbon cycling. We conclude that biotic disturbances can have major impacts on forest C stocks and fluxes and can be large enough to affect regional C cycling. However, additional research is needed to reduce the uncertainties associated with quantifying biotic disturbance effects on the N orth A merican C budget.

Fire Injury Reduces Inducible Defenses of Lodgepole Pine against Mountain Pine Beetle - Erinn N. Powell; Kenneth F. Raffa (Journal of Chemical Ecology, 2011)

Responses of Bark Beetle-Associated Bacteria to Host Monoterpenes and Their Relationship to Insect Life Histories - Aaron S. Adams; Celia K. Boone; Jörg Bohlmann; Kenneth F. Raffa (Journal of Chemical Ecology, 2011)

Symbiosis research, technology, and education: Proceedings of the 6th International Symbiosis Society Congress held in Madison Wisconsin, USA, August 2009 - Heidi Goodrich-Blair; Jean-Michel Ané; James D. Bever; Seth R. Bordenstein; Monika Bright; John M. Chaston; Keith Clay; Cameron R. Currie; Angela E. Douglas; Nicole Gerardo; Maria J. Harrison; Ruth E. Ley; et al. (Symbiosis, 2010)

A Literal Use of “Forest Health” Safeguards against Misuse and Misapplication - Kenneth F. Raffa; Brian Aukema; Barbara J. Bentz; Allan Carroll; Nadir Erbilgin; Daniel A. Herms; Jeffrey A. Hicke; Richard W. Hofstetter; Steven Katovich; B. Staffan Lindgren; Jesse Logan; William Mattson; et al. (Journal of Forestry, 2009)

Can chemical communication be cryptic? Adaptations by herbivores to natural enemies exploiting prey semiochemistry - Kenneth F. Raffa; Kenneth R. Hobson; Sara LaFontaine; Brian H. Aukema (Oecologia, 2007)

Phylogeography of spruce beetles ( Dendroctonus rufipennis Kirby) (Curculionidae: Scolytinae) in North America - LUANA S. MAROJA; STEVEN M. BOGDANOWICZ; KIMBERLY F. WALLIN; KENNETH F. RAFFA; RICHARD G. HARRISON (Molecular Ecology, 2007)
Tree‐feeding insects that are widespread in north temperate regions are excellent models for studying how past glaciations have impacted differentiation and speciation. We used mitochondrial DNA (mtDNA) sequences and allele frequencies at nine microsatellite loci to examine genetic population structure across the current range of the spruce beetle ( Dendroctonus rufipennis ), an economically important insect in North America. Two major haplotype groups occur across northern North America, from Newfoundland to Alaska, on white spruce ( Picea glauca ), and a third distinctive haplotype group occurs throughout the Rocky Mountains on Engelmann spruce ( Picea engelmannii ). The two mtDNA lineages found in northern populations are 3–4% divergent from each other and from the lineages found in the Rocky Mountains. Analyses of microsatellite data also suggest the existence of major population groupings associated with different geographical regions. In the Pacific Northwest, concordant contact zones for genetically distinct populations of spruce beetles and their principal hosts appear to reflect recent secondary contact. Although we could detect no evidence of historical mtDNA gene flow between allopatric population groups, patterns of variation in the Pacific Northwest suggest recent hybridization and introgression. Together with the pollen record for spruce, they also suggest that beetles have spread from at least three glacial refugia. A minimum estimate of divergence time between the Rocky Mountain and northern populations was 1.7 Myr (million years), presumably reflecting the combined effects of isolation during multiple glacial cycles.

Sources of Insect and Plant Volatiles Attractive to Cottonwood Leaf Beetles Feeding on Hybrid Poplar - Alexander P. Kendrick; Kenneth F. Raffa (Journal of Chemical Ecology, 2006)

Density-dependent effects of multiple predators sharing a common prey in an endophytic habitat - Brian H. Aukema; Murray K. Clayton; Kenneth F. Raffa (Oecologia, 2004)

Gender- and sequence-dependent predation within group colonizers of defended plants: a constraint on cheating among bark beetles? - Brian H. Aukema; Kenneth F. Raffa (Oecologia, 2004)

Behavior of Adult and Larval Platysoma cylindrica (Coleoptera: Histeridae) and Larval Medetera bistriata (Diptera: Dolichopodidae) During Subcortical Predation of Ips pini (Coleoptera: Scolytidae) - Brian H. Aukema; Kenneth F. Raffa (Journal of Insect Behavior, 2004)

Leaf Ontogeny Influences Leaf Phenolics and the Efficacy of Genetically Expressed Bacillus thuringiensis cry1A(a) d-Endotoxin in Hybrid Poplar Against Gypsy Moth - Karl W. Kleiner; David D. Ellis; Brent H. McCown; Kenneth F. Raffa (Journal of Chemical Ecology, 2003)

Phloeophagous and Predaceous Insects Responding to Synthetic Pheromones of Bark Beetles Inhabiting White Spruce Stands in the Great Lakes Region - Kirsten E. Haberkern; Kenneth F. Raffa (Journal of Chemical Ecology, 2003)

Relative effects of exophytic predation, endophytic predation, and intraspecific competition on a subcortical herbivore: consequences to the reproduction of Ips pini and Thanasimus dubius - Brian H. Aukema; Kenneth F. Raffa (Oecologia, 2002)

How many choices can your test animal compare effectively? Evaluating a critical assumption of behavioral preference tests - Kenneth F. Raffa; Nathan P. Havill; Erik V. Nordheim (Oecologia, 2002)

Modulation of predator attraction to pheromones of two prey species by stereochemistry of plant volatiles - Nadir Erbilgin; Kenneth F. Raffa (Oecologia, 2001)

Biotic disturbance agents in the boreal forest: considerations for vegetation change models - Carolyn M. Malmström; Kenneth F. Raffa (Global Change Biology, 2000)
Summary Disturbance regimes strongly determine vegetation patterns and succession in the boreal landscape. One of the current challenges for boreal vegetation modellers is to represent disturbance agents as dynamic factors that can respond to climate change. Outbreak species of insects and plant pathogens can cause marked changes in vegetation patterns and should be incorporated into vegetation change models. This introduction to the ecology of boreal biotic disturbance agents is designed as a brief overview for global change researchers and modellers. We discuss the importance of biotic disturbance agents in the boreal forest, offer an overview of their ecology, and review modelling approaches. We illustrate these issues with examples from different systems, drawing largely from our experience with bark beetles.

Opposing Effects of Host Monoterpenes on Responses by Two Sympatric Species of Bark Beetles to Their Aggregation Pheromones - Nadir Erbilgin; Kenneth F. Raffa (Journal of Chemical Ecology, 2000)

Chemically Mediated Predator-free Space: Herbivores Can Synergize Intraspecific Communication Without Increasing Risk of Predation - Brian H. Aukema; Kenneth F. Raffa (Journal of Chemical Ecology, 2000)

Perspective: Ethics and Genetically Engineered Plantations - Steven H. Strauss; Kenneth F. Raffa; Peter C. List (Journal of Forestry, 2000)

Effects of Host Tree Species on Attractiveness of Tunneling Pine Engravers, Ips pini, to Conspecifics and Insect Predators - Nadir Erbilgin; Kenneth F. Raffa (Journal of Chemical Ecology, 2000)

Effects of elicitation treatment and genotypic variation on induced resistance in Populus : impacts on gypsy moth (Lepidoptera: Lymantriidae) development and feeding behavior - Nathan P. Havill; Kenneth F. Raffa (Oecologia, 1999)

Sources of Variation in Concentration and Composition of Foliar Monoterpenes in Tamarack (Larix laricina) Seedlings: Roles of Nutrient Availability, Time of Season, and Plant Architecture - Jaimie S. Powell; Kenneth F. Raffa (Journal of Chemical Ecology, 1999)

Partitioning of 14 C-labeled photosynthate to allelochemicals and primary metabolites in source and sink leaves of aspen: evidence for secondary metabolite turnover - Karl W. Kleiner; Kenneth F. Raffa; Richard E. Dickson (Oecologia, 1999)

Altered Constitutive and Inducible Phloem Monoterpenes Following Natural Defoliation of Jack Pine: Implications to Host Mediated Interguild Interactions and Plant Defense Theories - Kimberly F. Wallin; Kenneth F. Raffa (Journal of Chemical Ecology, 1999)

Interactions Among Insect Herbivore Guilds: Influence of Thrips Bud Injury on Foliar Chemistry and Suitability to Gypsy Moths - Lynne K. Rieske; Kenneth F. Raffa (Journal of Chemical Ecology, 1998)

Effects of Constitutive and Inducible Traits of Hybrid Poplars on Forest Tent Caterpillar Feeding and Population Ecology - Daniel J. Robison; Kenneth F. Raffa (Forest Science, 1997)
Hybrid Populus spp. clones, differentially affected forest tent caterpillar, Malacosoma disstria, behavior, development, and population dynamics. Increased larval cohort size and larval silk generally enhanced development. Larval behavior affected developmental success. Under choice conditions, larvae selected more suitable clones, and their growth was enhanced when they moved from less to more suitable hosts. Herbivory by the forest tent caterpillar caused significant reductions in the quality of foliage for subsequent larval development. Polar and nonpolar foliar extracts varied between constitutive and previously damaged plants, and elicited significant larval behavioral responses. The extent to which prior feeding induced foliar changes that affected larval feeding and development varied among clones. The ability of forest tent caterpillar to exploit clones includes genetic and environmental components affecting foliar quality, and includes positive and negative density dependent feedback. In whole-tree field cages, forest tent caterpillar populations increased 9.7x during a 2 yr period on a highly suitable clone, and declined 2.7x on a poor quality clone. The relationships between clonal suitability and forest tent caterpillar population growth were strongly influenced by bud phenology and exudates, in addition to foliar traits. For. Sci. 43(2):252-267.